Studi Al-Qur’an dan Al-Hadits Kontemporer: Aliran Pendidikan: Nativisme, Empirisme, Konvergensi dan Fitrah dalam Pendidikan - Masithoh, Fisa Bela; Anshory, Muhammad Isa (TSAQOFAH, 2025)
Human beings are inherently perfect, dynamic, and possess the potential to change and develop. In the field of education, three classical developmental theories serve as foundational frameworks for understanding the origins and growth of human nature. First, Nativism, proposed by Arthur Schopenhauer, argues that human traits are innate and inherited from one’s parents. Second, Empiricism, advanced by John Locke, asserts that individuals develop entirely through experience and environmental influence, rather than heredity. Third, the Convergence theory, formulated by William Stern, combines both perspectives by emphasizing the interaction between hereditary and environmental factors. In the context of educational and scientific advancement, the convergence approach has become increasingly relevant for understanding the complexity of human development. Nevertheless, debates persist regarding which educational elements exert the most influence. This article aims to describe the concept of fitrah from an Islamic perspective as a fundamental distinction from Western views. According to Islam, every human is born with fitrah, a natural inclination toward tawhid, honesty, and goodness, and possesses innate potential that must be guided and nurtured through education. The implication of this concept is that Islamic education must be capable of preserving, managing, and developing human fitrah in alignment with the message of Islam and the divine purpose of humanity as servants and stewards (khalifah) on earth.